New directions in metabolic syndrome diagnosis: assessment of vascular endothelial growth factor, pentraxin-3 and transforming growth factor beta levels - R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2019)
The article presents the results of Russian and international clinical studies on the levels of angiogenesis markers (vascular endothelial growth factor, pentraxin 3 and transforming growth factor beta) in patients with metabolic syndrome.